Genetic diversity of locus of enterocyte effacement genes of enteropathogenic Escherichia coli isolated from Peruvian children. - Contreras, C. A. (2014)
The aim of this study was to determine the frequency and allele associations of locus of enterocyte effacement encoded esp and tir genes among 181 enteropathogenic Escherichia coli (EPEC) strains (90 diarrhoea-associated and 91 controls) isolated from Peruvian children under 18 months of age. We analysed espA, espB, espD and tir alleles by PCR-RFLP. EPEC strains were isolated with higher frequency from healthy controls (91/424, 21.7 %) than from diarrhoeal samples (90/936, 9.6 %) (P,0.001); 28.9% of diarrhoeal and 17.6% of control samples were typical EPEC (tEPEC). The distribution of espA alleles (alpha, beta, beta2 and gamma) and espD alleles (alpha, beta, gamma and a new variant, espD-N1) between tEPEC and atypical EPEC (aEPEC) was significantly different (P,0.05). espD-alpha was more common among acute episodes (P,0.05). espB typing resulted in five alleles (alpha, beta, gamma and two new suballeles, espB-alpha2 and espB-alpha3), while tir-beta and tir-gamma2 were the most common intimin receptor subtypes. Seventy-two combinations of espA, espB, espD and tir alleles were found; the most prevalent combination was espA-beta, espB-beta, espD-beta, tir-beta (34/181 strains), which was more frequent among tEPEC strains (P,0.05). Our findings indicate that there is a high degree of heterogeneity among EPEC strains isolated from Peruvian children and that aEPEC and tEPEC variants cluster.